PEMBUATAN DAN KARAKTERISASI SEL SUPERKAPASITOR MENGGUNAKAN KARBON AKTIF MONOLIT DARI KAYU KARET BERDASARKAN VARIASI KONSENTRASI HNO 3 - Arif, Eko Nur; Taer, Erman; Farma, Rakhmawati (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Synthesis of carbon electrode from rubber wood was started by carbonizing process by adding N 2 gas at a temperature of 600 Â°C and continued by utilizing physical activation of CO 2 gas at 850 Â°C for 2 hours, and followed by a combination process of chemical activation using potassium hydroxide activator and nitric acid (HNO 3 ) with its concentration of 5%, 15% and 25%. Density of resulted electrodes was 0.407 g/cm3, 0.359 g /cm3 and 0.349 g/cm3 for each sample. X-ray diffraction analysis showed amorphous carbon electrodes in the presence of ramps at 2Î¸ of 25.25 o and 44.21 o . The results of cyclic voltametry obtained specific capacitance of 10.444 F/g, 70.1969 F/g and 81.8234 F/g, respectively for each HNO 3 concentration. It was concluted that the addition of HNO3 to the activation proces can improve the performance of supercapacitors cell. The highest specific capacitance obtained 81.823 F/g for the 25% HNO3.